9 - Présentation de soi et techniques du corps : les élections Miss au Burkina Faso - Pépin Hien Ollo (Africa Development, 2021)
Beauty contests in Burkina Faso are a very important moment for girls, especially underprivileged girls, for whom they are a means of obtain- ing social recognition and finding a way out of poverty. That is why, in their view, any possible means can be used to win the competition. Paradoxically, the aesthetic canons that long presided over the desig- nation of beauty are being challenged and there is a growing tendency to copy the Western model. The aim of this contribution is to review the process that has led to a certain liberation of the body. In this regard, several physical techniques and games of seduction and domination are used, particularly since the body has become a form of capital used in social investment.